2017
DOI: 10.1093/mnras/stx445
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical star formation across the grand-design spiral NGC 1566

Abstract: We investigate how star formation is spatially organized in the grand-design spiral NGC 1566 from deep HST photometry with the Legacy ExtraGalactic UV Survey (LEGUS). Our contour-based clustering analysis reveals 890 distinct stellar conglomerations at various levels of significance. These star-forming complexes are organized in a hierarchical fashion with the larger congregations consisting of smaller structures, which themselves fragment into even smaller and more compact stellar groupings. Their size distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 95 publications
10
44
0
Order By: Relevance
“…2) Timescale arguments rule out the possibility that the photons ionizing the gas in the tails originate from massive stars in the disks of these galaxies. Based on this, as well as on our molecular gas detections in the tails (Moretti et al 2018b) and our deep FUV and NUV imaging (George et al 2018), we conclude that star formation occurs in situ in the tails, within the Hα clumps we identify.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…2) Timescale arguments rule out the possibility that the photons ionizing the gas in the tails originate from massive stars in the disks of these galaxies. Based on this, as well as on our molecular gas detections in the tails (Moretti et al 2018b) and our deep FUV and NUV imaging (George et al 2018), we conclude that star formation occurs in situ in the tails, within the Hα clumps we identify.…”
Section: Discussionsupporting
confidence: 71%
“…In the same fashion, the FUV and NUV light of the O and B young stars in the clumps of the tails was directly observed with UVIT@ASTROSAT in JO201, one of the galaxies in our sample (George et al 2018), where we found a remarkable agreeement between the SFR of individual clumps derived from the FUV and from Hα. GALEX data of several GASP jellyfishes, albeit at much lower spatial resolution, support the same scenario.…”
Section: In-situ Star Formation In the Tailssupporting
confidence: 78%
See 1 more Smart Citation
“…M 51 (NGC 5194 and NGC 5195) is part of the Legacy Ex-traGalactic UV Survey 1 (LEGUS, HST GO-13364; Calzetti et al 2015a), a Cycle 21 HST treasury program of 50 nearby (∼3.5-16 Mpc) galaxies in five UV and optical bands (NUV, U, B, V, and I) with the goal of investigating the connection between local star forming regions -as traced with young stellar clustersand global star formation within the nearby universe. Results with the LEGUS datasets so far include support for a hierarchical star formation process (Elmegreen et al 2014;Gouliermis et al 2017;Grasha et al 2015Grasha et al , 2017a with the age and size distribution of the hierarchies driven by turbulence (Gouliermis et al 2015b;Grasha et al 2017b); investigation of the effect on the evolution of galaxies from the radiative and mechanical feedback of star clusters (Calzetti et al 2015b); tests for variations in the initial mass function of star clusters (Krumholz et al 2015;Ashworth et al 2017); test spiral density wave theory (Shabani et al 2018); and extinction maps using stellar catalogues to investigate variations in the dust-to-gas ratio with metallicity (Kahre et al 2018). In this work, we perform a cross-correlation analysis between the star clusters from the LE-GUS catalogue and the GMC catalogue from the PAWS project in M 51.…”
Section: Introductionmentioning
confidence: 99%
“…In such a distribution, individual components of a population are more likely to appear near other members than if they were randomly distributed. Observations have directly measured the correlation in the spatial distribution between young stars, stellar clusters, and associations (e.g., Gomez et al 1993;Zhang et al 2001;Oey et al 2004;de la Fuente Marcos & de la Fuente Marcos 2009;Karampelas et al 2009;Bianchi et al 2012;Gouliermis et al 2015bGouliermis et al , 2017Gouliermis 2018;Grasha et al 2015Grasha et al , 2017aSun et al 2017a,b;Rodríguez et al 2018), providing overwhelming evidence for the coherence of star formation over multiple scales and across most galactic environments.…”
Section: Introductionmentioning
confidence: 99%